2016
DOI: 10.1111/sji.12466
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–Foetal Diabetes Modifies Neonatal Fc Receptor Expression on Human Leucocytes

Abstract: This study investigated the expression of the neonatal Fc receptor (FcRn) in maternal blood, cord blood and placental cells and determined IgG levels in maternal blood and cord blood from diabetic mothers. Peripheral blood, cord blood and placenta samples were collected from 26 mothers with normoglycaemia (non-diabetic, ND group) and 52 with hyperglycaemia (26 with mild gestational hyperglycaemia, MGH group, and 26 with type 2 diabetes mellitus, DM-2 group). Cells expressing CD19 + and FcRn were identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Stach et al ( 98 ) demonstrated an increased rate of IgG transfer in hyperglycemic mothers for all antigens they studied (GBS, Klebsiella LPS, and Pseudomonas LPS), as did França et al ( 114 ). More recently, De Souza et al investigated both the transfer of IgG and expression of FcRn expression (measured by flow cytometry), in normo- and hyperglycemic mothers ( 115 ). They found that mothers with pre-existing type 2 diabetes had lower total levels of IgG, and reduced leukocyte FcRn expression across maternal blood, cord blood, and placental samples (collected at delivery) compared with normoglycemic mothers.…”
Section: Factors Associated With Changes In Transplacental Antibody Tmentioning
confidence: 99%
“…Stach et al ( 98 ) demonstrated an increased rate of IgG transfer in hyperglycemic mothers for all antigens they studied (GBS, Klebsiella LPS, and Pseudomonas LPS), as did França et al ( 114 ). More recently, De Souza et al investigated both the transfer of IgG and expression of FcRn expression (measured by flow cytometry), in normo- and hyperglycemic mothers ( 115 ). They found that mothers with pre-existing type 2 diabetes had lower total levels of IgG, and reduced leukocyte FcRn expression across maternal blood, cord blood, and placental samples (collected at delivery) compared with normoglycemic mothers.…”
Section: Factors Associated With Changes In Transplacental Antibody Tmentioning
confidence: 99%
“…These usually reference one review (12) that has a graph illustrating data from a single study (13). We have identified 17 papers that have measured maternal and cord levels of the four IgG subclasses (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) (Figure 1). Calculating the mean from these papers produces transfer ratios of 1.36 for IgG1, 0.97 for IgG2, 1.12 for IgG3, and 1.12 for IgG4, although the high inter-study variation in both transfer ratios and the transfer hierarchy of the subclasses makes this average an oversimplification.…”
Section: Introductionmentioning
confidence: 99%
“…The immune composition of breast milk changes in the presence of GDM, a disease recognized as a global pandemic characterized not only by increased insulin resistance and glucose intolerance but also by a state of low-grade systemic inflammation and dysregulation of the immune system ( 12 , 35 ), which induces an imbalance between Th1 and Th2 cells favoring inflammatory responses. Furthermore, due to changes in glucose metabolism, the components of milk that these women produce are also altered ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the colostrum has high levels of immunoglobulins, cytokines, and immune cells compared to mature milk ( 9 , 10 ). Furthermore, the colostrum can protect the infant from allergic and chronic diseases and protect the infant from hypertension, type 2 diabetes, and excess weight ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%